Dyadic parent–infant interaction patterns at 12 months: Exploring dyadic parent–infant gender compositions. Issue 3 (12th May 2022) - Siqveland, Torill Sundet; Fredriksen, Eivor; Wentzel‐Larsen, Tore; Smith, Lars; Moe, Vibeke
Abstract: This study investigates differences in dyadic mother–infant and father–infant interaction patterns at infant age 12 months, and the relation between different parent–infant gender compositions and the dyadic interaction. Data were drawn from a large‐scale, population‐based Norwegian community sample comprising 671 mother–infant and 337 father–infant interactions. The Early Relational Health Screen (ERHS), a screening method for observing dyadic parent–infant interactions, was used to assess the parent–infant interactions. Scores on the ERHS were employed to investigate dyadic differences in the overall interaction scores, and dyadic interaction on seven sub‐dimensions between mother–infant and father–infant pairs. The relation between different parent–infant gender compositions and the dyadic interaction scores was also examined. As expected in a normative sample, most parent–infant interactions received scores in the upper rating levels. Differences between mother–infant and father–infant patterns were generally small, but mother–infant dyads tended to obtain slightly higher scores. The mother–infant dyads received higher scores on the dimensions of engagement and enjoyment, but no other significant differences between the parent–infant pairs were found for the remaining dimensions. We did not find evidence for a moderation effect of child gender. However, parent–daughter dyads received somewhat higher scores than the parent–son dyads. Resumen: Este estudio investiga las diferencias en los patrones de interacción de las díadas madre‐infante y padre‐infante a los 12 meses de edad del infante, y la relación entre las diferentes composiciones de género de progenitor‐infante y la interacción diádica. Los datos se obtuvieron de un grupo muestra a gran escala con base en la población en una comunidad noruega y el mismo comprendía 671 interacciones madre‐infante y 337 padre‐infante. La Temprana Detección de Salud de la Relación (ERHS), un método de examinación para observar las interacciones progenitor‐infante, se usó para evaluar las interacciones progenitor‐infante. Los puntajes de ERHS se emplearon para investigar las diferencias diádicas dentro de los puntajes de interacción generales, y las interacciones diádicas acerca de siete sub‐dimensiones entre los pares de madre‐infante y padre‐infante. También se examinó la relación entre las diferentes composiciones de género progenitor‐infante y la interacción diádica. Como se esperaba en un grupo muestra normativo, la mayoría de las interacciones progenitor‐infante recibió puntajes en los niveles superiores de la evaluación. Las diferencias entre los patrones madre‐infante y padre‐infante fueron generalmente pequeñas, pero las díadas madre‐infante tendieron a recibir puntajes un poquito más altos. Las díadas madre‐infante recibieron más altos puntajes en las dimensiones de participación y disfrute, pero no se encontraron otras diferencias significativas entre los pares progenitor‐infante en el resto de las dimensiones. No encontramos evidencia de un efecto de moderación del género del infante. Sin embargo, las díadas padre‐hija recibieron hasta cierto punto puntaje más altos que las díadas padre‐hijo. Résumé: Cette étude porte sur les différences dans les patterns d'interaction dyadique mère‐nourrisson et père‐nourrisson à l'âge de 12 mois pour le bébé, et la relation entre les différentes compositions de genre parent‐bébés et l'interaction dyadique. Les données ont été extraites d'un échantillon communautaire norvégien de grande taille, basé sur la population, comprenant 671 interactions mère‐nourrisson et 337 interactions père‐nourrisson. Le Dépistage Précoce de Santé Relationnelle (ERHS), une méthode de dépistage pour l'observation des interactions dyadiques parent‐bébé, a été utilisé afin d'évaluer les interactions parent‐bébé. Les scores au ERHS ont été employés pour rechercher les différences entre les scores d'interaction généraux et l'interaction dyadique concernant sept sous‐dimensions entre les paires mère‐bébé et père‐bébé. La relation entre les différentes compositions de genre parent‐bébé et les scores d'interaction dyadique a également été examinée. Comme prévu dans un échantillon normatif la plupart des interactions parent‐bébé ont reçu des scores dans les niveaux les plus hauts. Les différences entre les patterns mère‐bébé et père‐bébé étaient généralement petites mais les dyades mère‐bébé ont eu tendance à obtenir des scores un peu plus élevés. Les dyades mère‐bébé ont reçu de meilleurs scores quant aux dimensions d'engagement et de plaisir, mais aucune autre différence importante n'a été trouvée entre les paires parent‐bébé pour les autres dimensions. Nous n'avons pas trouvé de preuves d'un effet de modération pour le genre de l'enfant. Cependant les dyades parent‐fille ont reçu des scores un peu plus élevés que les dyades parent‐fils. Zusammenfassung: Muster in der dyadischen Eltern‐Kind‐Interaktion im Alter von 12 Monaten: Eine Exploration der Eltern‐Kind Geschlechterzusammensetzung Diese Studie untersucht im Säuglingsalter von 12 Monaten Unterschiede zwischen dyadischen Mutter‐Kind‐ und Vater‐Kind‐Interaktionsmustern sowie die Beziehung zwischen verschiedenen Eltern‐Kind‐Geschlechtszusammensetzungen und der dyadischen Interaktion. Die Daten stammen aus einer groß angelegten, repräsentativen norwegischen Bevölkerungsstichprobe mit 671 Mutter‐Kind‐ und 337 Vater‐Kind‐Interaktionen. Zur Beurteilung der Eltern‐Säuglings‐Interaktionen wurde der Early Relational Health Screen (ERHS) verwendet, eine Screening‐Methode zur Beobachtung dyadischer Eltern‐Säuglings‐Interaktionen. Mittels der ERHS‐Scores wurden dyadische Unterschiede zwischen Mutter‐Kind‐ und Vater‐Kind‐Paaren in den Gesamtinteraktionsergebnissen und dyadischen Interaktionen auf sieben Unterdimensionen untersucht. Außerdem wurde der Zusammenhang zwischen der unterschiedlichen Geschlechterzusammensetzung von Elternteil und Kind und den dyadischen Interaktionsergebnissen untersucht. Wie in einer Normstichprobe zu erwarten war, erhielten die meisten Eltern‐Kind‐Interaktionen Werte im oberen Ratingbereich. Die Unterschiede zwischen Mutter‐Kind‐ und Vater‐Kind‐Mustern waren im Allgemeinen gering, aber Mutter‐Kind‐Dyaden erhielten tendenziell etwas höhere Punktzahlen. Die Mutter‐Kind‐Paare erzielten höhere Werte auf den Dimensionen Engagement und Freude, aber für die übrigen Dimensionen wurden keine weiteren signifikanten Unterschiede zwischen den Eltern‐Kind‐Paaren festgestellt. Wir fanden keine Hinweise auf einen moderierenden Effekt des Geschlechts des Kindes. Allerdings erzielten Eltern‐Tochter‐Paare etwas höhere Werte als Eltern‐Sohn‐Paare. 抄録: 生後12ヶ月時の親−乳幼児の相互交流パターン:親‐乳幼児の性別構成の調査 本研究では、生後12ヶ月時における、母親‐乳幼児、父親‐乳幼児の相互交流パターンの違い、および親‐乳幼児の異なる性別構成と二者間の相互交流の関係について検討した。データは、ノルウェーの大規模集団研究で地域住民を対象とし、671組の母親‐乳幼児、337組の父親‐乳幼児の相互交流から得られた。親‐乳幼児の相互交流の評価には、親‐乳幼児の相互交流を観察するためのスクリーニング法であるEarly Relational Health Screen(ERHS)を用いた。ERHSを使用して、総合評点における二者間相互交流の違い、および７つの下位次元における母親‐乳幼児ペアと父親‐乳幼児ペアの二者間相互交流を調査した。また、異なる性別構成の親‐乳幼児と二者の相互交流評点の関係も検討された。標準的サンプルで予想されたように、ほとんどの親‐乳幼児相互交流は上位の評価レベルの評点であった。母‐乳幼児パターンと父‐乳幼児パターンの差は概して小さかったが、母−乳幼児の組の方がわずかに高評点となる傾向があった。母親‐乳幼児ペアでは、関わり合いと楽しさの次元で高い評点であったが、残りの次元では、親‐乳幼児ペア間の有意差は認められなかった。また、乳幼児の性別による調整効果は見られなかった。しかし、親‐娘ペアは親‐息子ペアよりやや高評点であった。 摘要: 本研究调查了婴儿12个月大时母婴和父婴二元互动模式的差异, 以及不同父母‐婴儿性别构成与二元互动之间的关系。数据来自大规模的、基于人群的挪威社区样本, 包括671组母婴互动和337组父婴互动。"早期关系健康筛查" (ERHS) 是一种观察二元亲子互动的筛查方法, 用于评估亲子互动。ERHS的分数被用来研究整体互动分数的二元差异, 以及母婴和父婴组别之间在七个子维度上的二元互动。此外, 还研究了不同父母‐婴儿性别构成与二元互动分数之间的关系。正如预期的那样, 在一个常模样本中, 大多数亲子互动都获得了较高等级的分数。母婴互动模式和父婴互动模式之间的差异通常很小, 但母婴组的得分往往略高。母婴组在参与和享受维度上的得分较高, 但在其余维度上, 没有发现父母‐婴儿组别之间的其他显著差异。我们没有发现儿童性别有调节作用的证据。不过, 父母‐女儿组的得分略高于父母‐儿子组。 ملخص: أنماط التفاعل الثنائي بين الوالدين والرضع في عمر 12 شهرًا: استكشاف التكوينات الجندرية بين الوالدين والرضع تبحث هذه الدراسة في الفروق في أنماط التفاعل الثنائي بين الأمهات والرضع والأب والرضيع في عمر 12 شهرًا ، والعلاقة بين التراكيب الجندرية المختلفة بين الوالدين والرضيع والتفاعل الثنائي. تم استخلاص المعطيات من عينة مجتمع نرويجي واسعة النطاق تعتمد على السكان تضم 671 تفاعلاً بين الأم والرضيع و 337 تفاعلاً بين الأب والرضيع. تم استخدام اختبار فحص الصحة العلائقية المبكرة (ERHS) ، وهي طريقة فحص لمراقبة التفاعلات الثنائية بين الوالدين والرضيع ، لتقييم التفاعلات بين الوالدين والرضيع. وتم استخدام النتائج للتحقيق في الفروق الثنائية في درجات التفاعل الكلي ، والتفاعلات الثنائية على سبعة أبعاد فرعية بين ثنائيات الأم والرضيع والأب والرضيع. كما تم فحص العلاقة بين التراكيب المختلفة للجنس بين الوالدين والرضيع ودرجات التفاعل الثنائي. كما هو متوقع في عينة معيارية ، حصلت معظم التفاعلات بين الوالدين والرضيع على درجات في مستويات التصنيف العليا. كانت الفروق بين أنماط الأم والرضيع والأب والرضيع صغيرة بشكل عام ، لكن ثنائية الأم والرضيع تميل إلى الحصول على درجات أعلى قليلاً. تلقت ثنائيات الأم والرضيع درجات أعلى في أبعاد المشاركة والمتعة ، ولكن لم يتم العثور على فروق ذات دلالة إحصائية أخرى بين ثنائيات الوالدين والرضيع للأبعاد المتبقية. لم نجد دليلاً على وجود تأثير معتدل لجنس الطفل. ومع ذلك ، فإن الثنائيات بين الوالدين والبنات حصلت على درجات أعلى إلى حد ما من الثنائيات بين الوالدين والأبناء.